2007
DOI: 10.1073/pnas.0609357104
|View full text |Cite|
|
Sign up to set email alerts
|

Arabidopsis SNI1 and RAD51D regulate both gene transcription and DNA recombination during the defense response

Abstract: ), the authors note that in Fig. 1D Right, the x-axis labels were transposed. The corrected figure and its legend appear below. MECs were isolated from BALB/c mice, cultured for 3 days, irradiated, and analyzed for %SP by Hoechst 33342 staining and flow cytometry. Radiation selectively increased the progenitor fraction (%SP) (P ϭ 0.015 for 2 Gy, 0.008 for 4 Gy, and 0.05 for 6 Gy by the two-tailed t test). (B) MCF-7 cells were analyzed for %SP by Hoechst 33342 staining and flow cytometry. Radiation selectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
153
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(158 citation statements)
references
References 29 publications
(47 reference statements)
5
153
0
Order By: Relevance
“…8; 43% of WT versus 72% of dKO at 80 mM mitomycin C), indicating enhanced mitomycin C tolerance. By contrast, the suppressor of sni1 1 (ssn1) mutant, which carries a mutation in RAD51, a key factor in R/R, was hypersensitive to mitomycin C, as previously reported 30 . This result indicate that the CRT1 family is involved in DNA repair, perhaps as a negative regulator.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…8; 43% of WT versus 72% of dKO at 80 mM mitomycin C), indicating enhanced mitomycin C tolerance. By contrast, the suppressor of sni1 1 (ssn1) mutant, which carries a mutation in RAD51, a key factor in R/R, was hypersensitive to mitomycin C, as previously reported 30 . This result indicate that the CRT1 family is involved in DNA repair, perhaps as a negative regulator.…”
Section: Resultssupporting
confidence: 70%
“…To assess whether CRT1/CRH1 are involved in DNA R/R, the dKO was monitored for altered resistance to the DNA-damaging agent, mitomycin C. Consistent with earlier studies, WT plants grown in the presence of mitomycin C exhibited reduced ability to form true leaves 30 . True leaf formation in dKO plants was suppressed to a lesser extent than in WT ( Fig.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…When a genetic screen was conducted to search for genetic suppressors of sni1, it was found that a loss-of-function mutation in RAD51D suppresses sni1 phenotypes completely. Both SNI1 and RAD51D were found to play roles in PR gene transcription and DNA recombination (Durrant et al, 2007). To identify additional negative regulators of PR gene expression and SAR, we screened for mutants that are hypersensitive to SA induction and found one with similar phenotypes to sni1.…”
mentioning
confidence: 99%
“…Among the genes found to be relevant in the SA response, there are several DNA repair (Song et al 2011) and chromatin remodeling genes. Since these proteins play a role in forming complex relevant for transcription (Durrant et al 2007), perhaps NRB4 is required for the proper function of these proteins.…”
Section: A Model Of Sa Responsementioning
confidence: 99%